Directed lithiation of a pyrene-1-carboxamide as a route to new pyrenyl fluorophores. (February 2016) - Wrona-Piotrowicz, Anna; Ciechańska, Magdalena; Zakrzewski, Janusz; Métivier, Rémi; Brosseau, Arnaud; Makal, Anna
Abstract: The lithiation of N-tert -butylpyrene-1-carboxamide with n BuLi-TMEDA in THF at −78 °C afforded, after quenching with chlorosilanes, the corresponding 2-(trialkylsilyl)pyrene-1-carboxamides. When DMF and diethyl oxalate were used as quenchers compounds having 8- tert -butyl-7-hydroxy-8, 9-dihydro-7 H -phenaleno-[1, 9- ef ]isoindole skeleton were obtained. The oxidation of compound having secondary OH group with Jones' reagent afforded 8- tert -butyl-7-hydroxy-8, 9-dihydro-7 H -phenaleno-[1, 9- ef ]isoindole-7, 9(8 H )dione. All of the synthesized compounds displayed fluorescence in solution ( λ max = 425–451 nm; ΦF = 15.1–40.8%) and in the solid state (( λ max = 410–555 nm; ΦF = 6–40%). The silylated amides display in the solid state monomer emission whereas in the case of the of phenalenoisoindole derivatives the emitting species are π-stacked aggregates. The formation of aggregates in the crystals of the latter compounds was confirmed by a single-crystal X-ray diffraction study. Graphical abstract: Highlights: Directed lithiation of a pyrene-1-carboxamide allows for selective C-2 substitution. Fused pyrene-2-pyrrolidone and −2, 5-pyrrolidinedione compounds have been prepared. The synthesized compounds are solution- and solid-state emitters. Bulky silyl C-2 substituents hamper π−π aggregation in the solid state.